The role of the central bank and commercial banks in promoting the use of electronic payments in Algeria in light of the monetary and banking law 23 (Journal of Economic Additions, 2025)
Through this study, we seek to identify the impact of technological development on traditional payment techniques, focusing on the efforts of the Algerian government in promoting the use of electronic payments, and the obligations of the Central Bank and commercial banks in promoting the use of this type of payment in light of the decisions of the Monetary and Banking Law 23-09.The results of the study showed that Algeria is witnessing an important development in the use of electronic payment technologies and Algeria's efforts to adopt financial technology, promote digitisation and achieve financial inclusion, accompanied by legal legislation and the efforts of the Central Bank and commercial banks to face new challenges, such as cybersecurity and information security, to ensure the success of the application of these technologies.Jel Classification Codes: G20, E42,G28.
Keywords: Keywords: Fintech, e-payments, cybersecurity.